SERAT MAKANAN DAN PERANNYA BAGI KESEHATAN - Clara Meliyanti Kusharto (Jurnal Gizi dan Pangan, 2006)
A study of fiber used epidemiological approach proved that in industrial countries occurence of  a western diseases were closely related to low fiber diet. The ideal intake of dietary fiber should be considered to produce weight of faeces equivalent to 140 – 150 g/day and a transit time less than 3 days, however others were stated that a variety of body response may also be considered in order to enhance a dietary fiber intake, since each component of dietary fiber gives a difference physiological effect in the body. Daily requirement intake of fiber is 25 – 30 g/man/day. Widyakarya (2004) stated that RDA of dietary fiber for adult and adolescence is 19 – 30 g/cap/day, and for children 10 – 14 g/1000 kcal. A diet contained high fiber has a positive effect to health. However, a further study is still needed with regards to antagonistic role if it is over consumed. Fiber has a unique roles as a component of prebiotic, which is useful for growth of intestinal microflora, and probiotic microflora.